2010
DOI: 10.1186/1687-9856-2010-940980
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Associated Birth Defects in Congenital Hypothyroidism

Abstract: Aim. To identify dysmorphic features and cardiac, skeletal, and urogenital anomalies in patients with congenital hypothyroidism. Patients and Methods. Seventeen children with congenital primary hypothyroidism were recruited. Cause for congenital hypothyroidism was established using ultrasound of thyroid and (99m)Tc radionuclide thyroid scintigraphy. Malformations were identified by clinical examination, echocardiography, X-ray of lumbar spine, and ultrasonography of abdomen. Results. Ten (59%) patients (6 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
9
0
4
Order By: Relevance
“…Many studies [8,12-23] reported that the frequencies of additional birth defects with CH were between 8% and 20%, except that of a recent study by Reddy (59%) [24]. The present result (17%) was well within this range.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Many studies [8,12-23] reported that the frequencies of additional birth defects with CH were between 8% and 20%, except that of a recent study by Reddy (59%) [24]. The present result (17%) was well within this range.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, PDA was found in one twin. A recent study by Reddy et al [24] reported that two out of ten patients had PDA in addition to CH. Other birth defects with CH in the present patients were hypospadias, cleft lip, and congenital genu recurvatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of congenital hypothyroidism ranges from 1:2,000–4,000 worldwide and mutations in different genes are responsible for one part (LaFranchi & Huang, ). In a study by Reddy et al () they found the incidence of NTD as 41% in infants with congenital hypothyroidism. In our study, the incidence of hypothyroidism was found to be 7.5% and this increase can be associated with genetic factors.…”
Section: Discussionmentioning
confidence: 98%
“…KH predominant olarak kardiyak, nöral tüp defektleri ve dismorfik özelliklerin bulunduğu çoklu konjenital malformasyonlarla ilişkilidir. KH'de konjenital kalp hastalıklarının yüksek prevalansta gö-rülmesi nedeniyle bu hastalara rutin ekokardiyografi uygulanması gerektiği bildirilmektedir (4) . Ayrıca tiroid hormonunun aktif formu olan triiyodotironinin spesifik olarak miyokarda etki ettiği ve hem direkt hem de indirekt olarak kardiyak fonksiyonu etkilediği gösteril-miştir (5,6) .…”
Section: Discussionunclassified